2016
DOI: 10.1123/jsep.2015-0175
|View full text |Cite
|
Sign up to set email alerts
|

Number of Years of Team and Individual Sport Participation During Adolescence and Depressive Symptoms in Early Adulthood

Abstract: The purpose of this study was to examine the longitudinal and unique association between number of years of team sport and individual sport participation during adolescence and depressive symptoms during early adulthood. Adolescents (n = 860) reported team sport and individual sport participation in each year of secondary school for five years. Participants reported depressive symptoms using the Major Depression Inventory three years after secondary school. Multivariate linear regression was performed to model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
65
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 29 publications
13
65
1
1
Order By: Relevance
“…In a recent study of a large representative sample of European adolescents, lower levels of anxiety and depression and higher levels of well-being were found among team sport participants 13. Team sport participation during adolescence has also been shown to be associated with lower levels of depressive symptoms in early adulthood 50 52. In line with this, our findings highlight that the type of sport, including the social aspect of participation, should be considered when examining the impact of sports on mental health among adolescents.…”
Section: Discussionsupporting
confidence: 84%
“…In a recent study of a large representative sample of European adolescents, lower levels of anxiety and depression and higher levels of well-being were found among team sport participants 13. Team sport participation during adolescence has also been shown to be associated with lower levels of depressive symptoms in early adulthood 50 52. In line with this, our findings highlight that the type of sport, including the social aspect of participation, should be considered when examining the impact of sports on mental health among adolescents.…”
Section: Discussionsupporting
confidence: 84%
“…The findings of this study showed a higher occurrence of common mental disorders in the portion of the population that did not practice sports. Corroborating our study, Sabiston et al 25 found that participation in team sports during high school can protect against depressive symptoms in early adulthood, probably because team sport provides group work, opportunity for interaction with people and better perceived social acceptance. Leisure time physical activity and participation in sports also contributed to a greater sense of well-being and lower levels of anxiety and depression among European adolescents 26 .…”
Section: Discussionsupporting
confidence: 82%
“…Although it is often stated in the scientific literature that team sports are more effective than other sports branches in developing social skills and provide an opportunity for young people to learn to work well with others and effectively contribute to a group (Vella et al, 2017;Sabiston et al, 2016), the distinguished social component of team sports can influence the obtained results of the conducted research (Sabiston et al, 2019). First, in team sport, competition is particularly fierce not only between individual teams but also within the team, between teammates, because each athlete's behaviour in sport can be also determined by the number of competitors participating in the collective system (Garcia et al, 2013).…”
Section: Discussionmentioning
confidence: 99%